Impact of preformed donor-specific anti-human leukocyte antigen antibodies on the clinical outcomes in pediatric liver transplantation patients: a retrospective cohort study - Kang, Zhong-Yu; Liu, Chun; Liu, Wei; Han, Xueya; Li, Daihong (Frontiers in Immunology, 2026)
PurposeThe impact of donor-specific anti-human leukocyte antigen (HLA) antibodies (DSAs) in pediatric liver transplantation (LT) have been widely studied. The effect of preformed DSAs in pediatric LT is still controversial. This study aimed to evaluate the prevalence of preformed DSAs and their impact on clinical outcomes in pediatric LT recipients.MethodsThis single-center retrospective cohort study included 243 pediatric patients who underwent LT between January 2019 and December 2022. The patients were divided into two groups according to the result of the pretransplant HLA antibody determined by Luminex™ Single Antigen Bead assay. The clinical outcomes, rejection, graft loss, patient survival, and the evolution of preformed DSAs were analyzed.ResultsThirty-one (12.7%) of the 243 patients had preformed DSAs, with most identified as class II DSAs. Among the patients with preformed DSAs, four had persistent preformed DSA, two had de novo DSAs, and 25 patients had cleared DSAs. Patients with and without preformed DSAs had comparable demographic characteristics but showed statistically significant differences by donor type (p = 0.042), intraoperative blood loss (p = 0.044), red blood cell transfusion (p = 0.006), and blood type (AB) (p = 0.035). Preformed DSAs were significantly associated with a longer intensive care unit stay (p = 0.008). No patients in either group developed antibody-mediated rejection post-transplantation. While the incidence of T cell-mediated rejection was higher in the preformed DSA-positive group compared to the negative group, this difference was not statistically significant (29.0% vs. 15.6%, p = 0.064). Other clinical outcomes and laboratory values were similar between the groups, with no association between preformed DSAs and overall graft loss or patient survival.ConclusionThis study showed that preformed DSAs were not associated with histologic or clinical outcomes in pediatric LT patients. Further studies with a larger sample size to obtain more reliable results are required to verify the risk associated with preformed DSAs in pediatric LT patients.